Family planning services in Sri Lanka: Clients nonmedical expectations and the health systems responsiveness (South East Asia Journal of Public Health, 2013)
Nonmedical expectations of the service seekers is an integral component of care that must be given due respect by the healthcare providers in delivering health services. This paper presents findings of a qualitative study conducted exploring the many dimensions of health systems responsiveness (HSR) in relation to family planning (FP) services provided by the government public health sector of Sri Lanka. Clients visiting the government FP clinics in Colombo district were interviewed using a semi structured moderator guide. Interviews covered three core domains of HSR including (i) clinic environment, (ii) ease of access to services and (iii) clients choice. Content analysis was carried out identifying themes around the domains. In relation to domain clinic environment, three subthemes were identified. These included (i) expectations from a free service, (ii) disorganization and (iii) sanitary facilities. Similarly, five subthemes emerged under the domain ease of access to services, namely, (i) outreach clinics, (ii) domiciliary services, (iii) social networking at MCH clinics, (iv) poly clinic/combined clinic setting and (v) working clients. In relation to the domain clients choice three subthemes emerged including, (i) service provider selecting the method, (ii) selecting the service provider and (iii) selecting the clinic. The findings emphasize that the healthcare providers must be enlightened on nonmedical aspects of service delivery and HSR must be taken into consideration in delivering FP services.South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 54-59 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15266